Altered Intrinsic and Casual Functional Connectivities of the Middle Temporal Visual Motion Area Subregions in Chess Experts - Song, Limei; Ge, Yanming; Long, Jinfeng; Dong, Peng (Frontiers in Neuroscience, 2020)
An outstanding chess player needs to accumulate massive visual and spatial information for chess configurations. Visual motion area (MT) is considered as a brain region specialized for visual motion perception and visuospatial attention processing. However, how long-term chess training shapes the functional connectivity patterns of MT, especially its functional subregions has rarely been investigated. In our study, using resting-state functional connectivity (RSFC) and granger causality analysis (GCA), we studied the changed functional couplings of MT subregions between 28 chess master players and 27 gender- and age-matched healthy novices to reveal the neural basis of long-term professional chess training. RSFC analysis identified decreased functional connections between right dorsal-anterior subregion (CI1.R) and left angular gyrus, and increased functional connections between right ventral-anterior MT subregion (CI2.R) and right superior temporal gyrus in chess experts. GCA analyses found increased mutual interactions of left angular gyrus and CI1.R in chess experts. Moreover, the decreased functional connections between left angular gyrus and CI1.R were negatively correlated with training time. These findings demonstrate that long-term professional chess training could enhance spatial perception and reconfiguration and semantic processing efficiency for superior performance.